2013
DOI: 10.1073/pnas.1318830110
|View full text |Cite
|
Sign up to set email alerts
|

Fungal-derived semiochemical 1-octen-3-ol disrupts dopamine packaging and causes neurodegeneration

Abstract: Parkinson disease (PD) is the most common movement disorder and, although the exact causes are unknown, recent epidemiological and experimental studies indicate that several environmental agents may be significant risk factors. To date, these suspected environmental risk factors have been man-made chemicals. In this report, we demonstrate via genetic, biochemical, and immunological studies that the common volatile fungal semiochemical 1-octen-3-ol reduces dopamine levels and causes dopamine neuron degeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 55 publications
4
60
0
Order By: Relevance
“…Thus, it has been suggested that an increase in VMAT activity may have neuroprotective effects (Guillot and Miller, 2009). This has been tested in vitro in cell cultures using mammalian VMAT and dVMAT (Mosharov et al, 2009; Park et al, 2007), and in vivo in the fly (Inamdar et al, 2013; Lawal et al, 2010; Sang et al, 2007). Over-expression of dVMAT rescues the loss of DA neurons caused by either a genetic or chemical insult (Inamdar et al, 2013; Lawal et al, 2010; Sang et al, 2007).…”
Section: Drosophila Vesicular Neurotransmitter Transportersmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it has been suggested that an increase in VMAT activity may have neuroprotective effects (Guillot and Miller, 2009). This has been tested in vitro in cell cultures using mammalian VMAT and dVMAT (Mosharov et al, 2009; Park et al, 2007), and in vivo in the fly (Inamdar et al, 2013; Lawal et al, 2010; Sang et al, 2007). Over-expression of dVMAT rescues the loss of DA neurons caused by either a genetic or chemical insult (Inamdar et al, 2013; Lawal et al, 2010; Sang et al, 2007).…”
Section: Drosophila Vesicular Neurotransmitter Transportersmentioning
confidence: 99%
“…This has been tested in vitro in cell cultures using mammalian VMAT and dVMAT (Mosharov et al, 2009; Park et al, 2007), and in vivo in the fly (Inamdar et al, 2013; Lawal et al, 2010; Sang et al, 2007). Over-expression of dVMAT rescues the loss of DA neurons caused by either a genetic or chemical insult (Inamdar et al, 2013; Lawal et al, 2010; Sang et al, 2007). Conversely, loss of dVMAT activity increases the toxicity of both genetic and chemical insults to DA cells (Inamdar et al, 2013; Lawal et al, 2010; Sang et al, 2007).…”
Section: Drosophila Vesicular Neurotransmitter Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous work from our laboratory, we developed a Drosophila bioassay system using third instar larvae for testing the toxicity of volatile phase compounds and showed that aerial exposure to vapors of both industrial solvents and fungal VOCs could cause delays in metamorphosis and death of larvae, pupae, and adults [31] and that 1-octen-3-ol disrupts dopamine packaging and causes neurodegeneration in flies [32]. Here we confirm the high toxicity of 1-octen-3-ol to Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the neurotoxicity of low concentrations of octenol has been shown in a Drosophila melanogaster model (Inamdar et al, 2010) as well as in human embryonic stem cells (Inamdar et al, 2012) and murine splenic leukocytes (Gorham and Hokeness, 2012). Finally, Inamdar et al demonstrated that octenol exerts toxicity via disruption of dopamine homeostasis and may represent a naturally occurring environmental agent involved in parkinsonism (Inamdar et al, 2013). Therefore, it is clear the importance of a low-cost system for the detection and discrimination of octenol in indoor air in buildings.…”
Section: Introductionmentioning
confidence: 99%